The impact of ChatGPT on higher education - Dempere, Juan; Modugu, Kennedy; Hesham, Allam; Ramasamy, Lakshmana Kumar (Frontiers in Education, 2023)
This study explores the effects of Artificial Intelligence (AI) chatbots, notably OpenAI's ChatGPT, on Higher Education Institutions (HEIs), employing a scoping review to determine trends and research gaps. The paper highlights ChatGPT's transformative architecture and versatile applications. The literature review presents diverse perspectives on ChatGPT's educational potential, with benefits like research support, automated grading, and enhanced human-computer interaction. Simultaneously, concerns arise about misuse, including online testing security and plagiarism. The research also examines the chatbots' broader societal and economic impacts, from job displacement to the digital literacy gap and AI-induced anxiety. It acknowledges AI's global expansion and the need for balanced regulation. Faculty members are urged to use AI tools proactively and ethically, to prevent academic fraud. The paper discusses potential advantages such as streamlined enrollment, improved student services, teaching enhancements, research aid, increased student retention, and risks, including privacy breaches, misuse, bias, misinformation, decreased human interaction, and accessibility issues. Despite its limitations, such as an incomplete representation of AI's effects on education and lack of concrete integration guidelines, the study concludes that AI technologies like ChatGPT offer significant benefits and risks, advocating for thoughtful, responsible integration within HEIs.